Cyberspace Security and Defense: Research Issues Proceedings of the NATO Advanced Research Workshop on Cyberspace Security and Defense: Research Issues Gdansk, Poland 6-9 September 2004 - Kowalik, Janusz S.; Gorski, Janusz; Sachenko, Anatoly; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Cyberspace security is a critical subject of our times. On one hand the development of Internet, mobile communications, distributed computing, computer software and databases storing essential enterprise information has helped to conduct business and personal communication between individual people. On the other hand it has created many opportunities for abuse, fraud and expensive damage. This book is a selection of the best papers presented at the NATO Advanced Research Workshop dealing with the Subject of Cyberspace Security and Defense. The level of the individual contributions in the volume is advanced and suitable for senior and graduate students, researchers and technologists who wish to get some feeling of the state of the art in several sub-disciplines of Cyberspace security. Several papers provide a broad-brush description of national security issues and brief summaries of technology states. These papers can be read and appreciated by technically enlightened managers and executives who want to understand security issues and approaches to technical solutions. An important question of our times is not "Should we do something for enhancing our digital assets security", the question is "How to do it".
General Security Issues -- IT Security Development -- A Case for Public and Private Review of Developing it Security Standards -- Assuring Critical Information Infrastructure -- Systemic Challenges for Critical Information Infrastructure Protection -- Decentralized Energy Supply to Secure Computer Systems -- Dependability -- Safety Analysis Methods-Software Development Questions -- Trust Case-A Case for Trustworthiness of IT Infrastructures -- Dependability, Structure, and Infrastructure -- Design for Safety and Security of Complex Embedded Systems: A Unified Approach -- Networks -- Design of Distributed Sensor Networks for Security and Defense -- A Distributed Approach to the Recognition of Geographically Located IP Devices -- Situational Awareness and Network Traffic Analysis -- Early Warning Information Systems and Secure Access Control -- Honeynets: Foundations for the Development of Early Warning Information Systems -- IRIS Biometrics for Secure Remote Access -- New Directions in Access Control -- Cryptography -- Improved Block Cipher Counter Mode of Operation Schemes -- Electronic Signature in Real World -- A Note on Two Significant Developments in Cyberspace Security and Defense -- A Cryptographic Mobile Agent Implementing Secure Personal Content Delivery Protocol -- Intrusion Detection -- An Infrastructure for Distributed Event Acquisition -- Some Aspects of Neural Network Approach for Intrusion Detection.
Keywords: COMPUTER SCIENCE; SOFTWARE ENGINEERING; DATA STRUCTURES (COMPUTER SCIENCE).; DATA ENCRYPTION (COMPUTER SCIENCE).; INFORMATION SYSTEMS; COMPUTER SCIENCE; SPECIAL PURPOSE AND APPLICATION-BASED SYSTEMS; DATA STRUCTURES, CRYPTOLOGY AND INFORMATION THEORY; DATA ENCRYPTION; INFORMATION SYSTEMS APPLICATIONS (INCL.INTERNET).